João Baptista do Rio e o Programa Pictórico Revivalista da Matriz de Viana do Castelo. - Rosas, Lúcia (2008)
João Baptista do Rio, a scenographic painter, as developed in the restauration (1880) of the parish church of Viana do Castelo a pictorical program according with a neo-gothic and neo-manuelino taste.